ZnO Nanowires/N719 Dye With Different Aspect Ratio as a Possible Photoelectrode for Dye-Sensitized Solar Cells - Portillo-Cortez, Karina; Martínez, Ana; Bizarro, Monserrat; García-Sánchez, Mario F.; Güell, Frank; Dutt, Ateet; Santana, Guillermo (Frontiers in Chemistry, 2021)
The vapor-liquid-solid (VLS) process was applied to fabricate zinc oxide nanowires (ZnO NWs) with a different aspect ratio (AR), morphological, and optical properties. The ZnO NWs were grown on a system that contains a quartz substrate with transparent conductive oxide (TCO) thin film followed by an Al-doped ZnO (AZO) seed layer; both films were grown by magnetron sputtering at room temperature. It was found that the ZnO NWs presented high crystalline quality and vertical orientation from different structural and morphological characterizations. Also, NWs showed a good density distribution of 69 NWs/μm2 with a different AR that offers their capability to be used as possible photoelectrode (anode) in potential future device applications. The samples optical properties were studied using various techniques such as photoluminescence (PL), absorption, and transmittance before and after sensitization with N719 dye. The results demonstrated that NW with 30 nm diameter had the best characteristics as feasible photoelectrode (anode) (high absorption, minimum recombination, high crystallinity). Also, the present samples optical properties were found to be improved due to the existence of N719 dye and Au nanoparticles on the tip of NWs. NWs grown in this work can be used in different photonic and optoelectronic applications.